Peningkatan Mutu Produk dan Pemasaran Olahan Ikan Bandeng - Asnawi, Asnawi; Saud, Ilham Maulana; Wiratmanto, Wiratmanto (Universitas Muhammadiyah Yogyakarta, 2017)
As well as micro, small, and medium-scale business in general, business groups engaged in the food processed milkfish also face the problems, especially on the limitations of product quality and marketing. Two businesswomen who pursue food business of milkfish, namely Mrs. Eko with Pindang Bandeng â€œWarisanâ€ and Mrs. Erni with presto milkfish â€œPrimaâ€. In production aspects, both businesses are still limited because it only meets the society needs and sell at certain moments like, Sunday morning recitation and tiban market. From the results of the pre-survey and interviews can be identified several problems, such as: unavailability of equipment to produce high quality products, unavailability of attractive packaging to enter broader market, unavailability aspect of legality of P-IRT from Health Office for micro food business, lack of entrepreneurship, and the need for more intensive management assistance to enter the wider market.These issues have been assisted by the completion of the following activities: improvement of equipment, package and nameplate, P-IRT certification, training to cultivate entrepreneurship, promotion, and marketing management assistance. Dedication program with IbM scheme has been implemented and produced the output, such as in the form of packaged the processed of milkfish, brochures, business name-plate of Pindang Bandeng and presto milkfish with brand â€œWarisanâ€ and â€œPrimaâ€, and P-IRT certificates for both partners.Keyword: product, marketing, processed milkfish